If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 11 = 195 Reorder the terms: 11 + 4x = 195 Solving 11 + 4x = 195 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11' to each side of the equation. 11 + -11 + 4x = 195 + -11 Combine like terms: 11 + -11 = 0 0 + 4x = 195 + -11 4x = 195 + -11 Combine like terms: 195 + -11 = 184 4x = 184 Divide each side by '4'. x = 46 Simplifying x = 46
| 3x+17=x+53 | | (x-12)/(3-x)=(x+33)/(x+3) | | (x^4)+(-10x^2)+(9)=0 | | x+3x+17=109 | | 20c=398 | | 8x-9=4x-7 | | 398c=20 | | 100=-5x | | 4x+2y=-3 | | 2x+65=6x+9 | | 3x-24=x+4 | | -7.3-5.18=-51.9 | | 4(4w+5)+3w=8(w+7)-3 | | 3x^3-51x=0 | | 20c=183 | | 22=2(4a+2) | | 20c=89 | | 5x+3-2x+11=x-6+x+14 | | 183w=4 | | -3x+1=-26 | | x^4-6x^2=-4 | | 4c=89 | | -3(7-2y)=-14-1 | | .05x+10(200-x)=.45x | | (x^4)+(-10x^2)+(16)=0 | | 2(y-3)=4x | | -1(8m+4)=4m-2(6m+2) | | -2x+7=2 | | (x^4)-(12x^2)+(11)=0 | | 0.5y+1=4x-2 | | 2x-5y=28 | | -5(x+4)=7-(-5) |